2021
DOI: 10.3390/su132111760
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Removal of Carbamazepine from Aqueous Solution by Using Activated Carbon and Biochar

Abstract: Carbamazepine (CBZ), one of the most used pharmaceuticals worldwide and a Contaminant of Emerging Concern, represents a potential risk for the environment and human health. Wastewater treatment plants (WWTPs) are a significant source of CBZ to the environment, polluting the whole water cycle. In this review, the CBZ presence and fate in the urban water cycle are addressed, with a focus on adsorption as a possible solution for its removal. Specifically, the scientific literature on CBZ removal by activated carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 252 publications
0
12
0
Order By: Relevance
“…Regarding biochar, Décima et al reported a wide range of specific surface area (i.e., S BET = 0.9–470.4 m 2 /g) [ 82 ]. Naghdi et al reported a low specific surface area, i.e., S BET = 47.25 m 2 /g, for pinewood biochar produced at 550 °C [ 120 ], while Chen et al reported S BET values equal to 1.82, 7.08, and 64.72 m 2 /g, depending on the pyrolysis temperature, i.e., 200, 300, and 500 °C [ 121 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding biochar, Décima et al reported a wide range of specific surface area (i.e., S BET = 0.9–470.4 m 2 /g) [ 82 ]. Naghdi et al reported a low specific surface area, i.e., S BET = 47.25 m 2 /g, for pinewood biochar produced at 550 °C [ 120 ], while Chen et al reported S BET values equal to 1.82, 7.08, and 64.72 m 2 /g, depending on the pyrolysis temperature, i.e., 200, 300, and 500 °C [ 121 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption–desorption isotherms were acquired in a relative pressure ( p / p 0 ) range from 0.01 to 0.99 [ 82 ]. Isotherm analyses were performed using the 3Flex Version 4.05 software.…”
Section: Methodsmentioning
confidence: 99%
“…Activated carbon is one of the common methods for adsorbing organic pollutants in drinking water, including pharmaceutically active compounds. The removal of carbamazepine by carbonbased sorbents was tested at various conditions with relatively high sorption capacities of up to 2 mmol g −1 [32][33][34]. Different clays and organoclay are also used as potential adsorbents for pharmaceutical pollution as a low-cost and effective technique.…”
Section: Introductionmentioning
confidence: 99%
“…Several commercially available biochars derived from waste wood are characterized for physical and chemical properties that can signify their relevant environmental applications. Parameters characterized include: physical properties (particle size distribution, specific gravity, density, porosity, surface area), hydraulic properties (hydraulic conductivity and water holding capacity), and chemical and electrochemical properties (organic matter and organic carbon contents, pH, oxidation-reduction potential and electrical conductivity, zeta potential, carbon, nitrogen and hydrogen (CHN) elemental composition, polycyclic aromatic hydrocarbons (PAHs), heavy metals, and leachable PAHs and heavy metals) [28]. A wide range of fixed carbon (0-47.8%), volatile matter (28-74.1%), and ash contents (1.5-65.7%) were observed among tested biochars.…”
Section: Introductionmentioning
confidence: 99%